1991
DOI: 10.1007/bf02337618
|View full text |Cite
|
Sign up to set email alerts
|

HLA antigens in Italian multiple sclerosis patients

Abstract: We analyzed HLA-A, -C, -B, -DR and -DQ specificities in 104 Italian multiple sclerosis patients and in 905 healthy controls. The frequencies of HLA-A23, A26, Cw4, DR3 and, especially DR5 antigens were significantly higher in multiple sclerosis patients than in controls. Patients with progressive course were characterized by high frequencies of B7, B8 and DR3 antigens: Cw1 and DRw11 shows a negative correlation with the extent of intrathecal IgG production. These data confirm that the HLA system may influence t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…If DR antigens themselves are directly involved in susceptibility to CNMS, the finding of DR4 association among patients of Mediterranean origin versus DR2 association in North Europe and North America may support the idea that MS within Europe is a heterogenous condition. Further studies of MS patients from the Mediterranean area seem indicated also because some studies of patients from Northern Italy indicate an association to B7 in patients with a progressive course, but with no association to DR2 or DR4 (24).…”
Section: Discussionmentioning
confidence: 99%
“…If DR antigens themselves are directly involved in susceptibility to CNMS, the finding of DR4 association among patients of Mediterranean origin versus DR2 association in North Europe and North America may support the idea that MS within Europe is a heterogenous condition. Further studies of MS patients from the Mediterranean area seem indicated also because some studies of patients from Northern Italy indicate an association to B7 in patients with a progressive course, but with no association to DR2 or DR4 (24).…”
Section: Discussionmentioning
confidence: 99%
“…The precise patho gene sis is unclear. Recent studies support the ideas that certain human leucocytlocu s A (HLA) haplotypes imply increased susceptibility to multiple sclerosis (1)(2)(3)(4)(5) and that infection s (6)(7)(8)(9)(10)(11)(12)(13)(14)(15), for example , retro virus (16)(17)(18) , may play a role in the patho genesis. There are several observations regarding the associated occurrence of multipl e sclerosis with other autoimmune disorders ( 19), like myas then ia gravis (20), thyroid disease (2 1), and Sjogren ' s syndrome (22), but also with such clearly HLA-Iinked conditions as ankylosing spondylitis (23) and narcolepsy (24,25 ).…”
mentioning
confidence: 80%
“…The present results for A23 allele are coherent with the study of HLA genes in MS patients in Italy. 17 La Mantia et al showed that the occurrence of A23, A26, Cw4, DR3 and DR5 alleles were significantly higher in MS patients than in controls. 17 We also have found that the prevalence of B51 allele in the normal population is much higher than in the ON patients in the present study (Table 1).…”
Section: Resultsmentioning
confidence: 98%
“…17 La Mantia et al showed that the occurrence of A23, A26, Cw4, DR3 and DR5 alleles were significantly higher in MS patients than in controls. 17 We also have found that the prevalence of B51 allele in the normal population is much higher than in the ON patients in the present study (Table 1). The logistic model shows a negative correlation between this allele and the development of ON (OR 0.05, 95% CI 0.00 Á/0.38, P B/ 0.004; Table 5).…”
Section: Resultsmentioning
confidence: 98%